Crystalline Diuranium Phosphinidiide and μ‐Phosphido Complexes with Symmetric and Asymmetric UPU Cores. Issue 35 (24th July 2017) - Rookes, Thomas M.; Gardner, Benedict M.; Balázs, Gábor; Gregson, Matthew; Tuna, Floriana; Wooles, Ashley J.; Scheer, Manfred; Liddle, Stephen T.
Abstract: Reaction of [U(Tren TIPS )(PH2 )] (1, Tren TIPS =N(CH2 CH2 NSiPr i 3 )3 ) with C6 H5 CH2 K and [U(Tren TIPS )(THF)][BPh4 ] (2 ) afforded a rare diuranium parent phosphinidiide complex [U(Tren TIPS )2 (μ‐PH)] (3 ). Treatment of3 with C6 H5 CH2 K and two equivalents of benzo‐15‐crown‐5 ether (B15C5) gave the diuranium μ‐phosphido complex [U(Tren TIPS )2 (μ‐P)][K(B15C5)2 ] (4 ). Alternatively, reaction of [U(Tren TIPS )(PH)][Na(12C4)2 ] (5, 12C4=12‐crown‐4 ether) with [UN(CH2 CH2 NSiMe2 Bu t )2 CH2 CH2 NSi(Me)(CH2 )(Bu t )] (6 ) produced the diuranium μ‐phosphido complex [U(Tren TIPS )(μ‐P)U(Tren DMBS )][Na(12C4)2 ] [7, Tren DMBS =N(CH2 CH2 NSiMe2 Bu t )3 ]. Compounds4 and7 are unprecedented examples of uranium phosphido complexes outside of matrix isolation studies, and they rapidly decompose in solution underscoring the paucity of uranium phosphido complexes. Interestingly, 4 and7 feature symmetric and asymmetric UPU cores, respectively, reflecting their differing steric profiles. Abstract : Outside the matrix : Prepared by two different routes, the first examples of uranium phosphido complexes outside of cryogenic matrix isolation conditions are reported, revealing symmetric and asymmetric (shown; U green, P purple, N blue, Si yellow) UPU cores in the solid‐state crystal structures.